Global trends in museum diplomacy : post-Guggenheim developments - Grincheva, Natalia (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Global Trends in Museum Diplomacy traces the transformation of museums from publicly or privately funded heritage institutions into active players in the economic sector of culture. Exploring how this transformation reconfigured cultural diplomacy, the book argues that museums have become autonomous diplomatic players on the world stage. The book offers a comparative analysis across a range of case studies in order to demonstrate that museums have gone global in the era of neoliberal globalisation. Grincheva focuses first on the Solomon R. Guggenheim Foundation, which is well known for its bold revolutionising strategies of global expansion: museum franchising and global corporatisation. The book then goes on to explore how these strategies were adopted across museums around the world and analyses two cases of post-Guggenheim developments in China and Russia: the K11 Art Mall in Hong Kong and the International Network of Foundations of the State Hermitage Museum in Russia. These cases from more authoritarian political regimes evidence the emergence of alternative avenues of museum diplomacy that no longer depend on government commissions to serve immediate geo-political interests. Global Trends in Museum Diplomacy will be a valuable resource for students, scholars and practitioners of contemporary museology and cultural diplomacy. Documenting new developments in museum diplomacy, the book will be particularly interesting to museum and heritage practitioners and policymakers involved in international exchanges or official programs of cultural diplomacy"--
Introduction: museum diplomacy then and now -- Cultural diplomacy of a different kind -- Museum diplomacy as a corporate enterprise -- Museum diplomacy as a global franchising -- Conclusion: museum diplomacy in the neoliberal age.
"Routledge Focus".
OCLC-licensed vendor bibliographic record.
Keywords: Solomon R. Guggenheim Foundation; Museums -- Public relations; Cultural diplomacy; LANGUAGE ARTS & DISCIPLINES / Library & Information Science; SOCIAL SCIENCE / Archaeology